America the Ingenious: How a Nation of Dreamers, Immigrants, and Tinkerers Changed the World - Kevin Baker (Artisan, 2016)
All made in America: The skyscraper and subway car. The telephone and telegraph. The safety elevator and safety pin. Plus the microprocessor, amusement park, MRI, supermarket, Pennsylvania rifle, and Tennessee Valley Authority. Not to mention the city of Chicago or jazz or that magnificent Golden Gate Bridge.